1992
DOI: 10.1007/bf00201802
|View full text |Cite
|
Sign up to set email alerts
|

Complex dynamics underlying the human electrocardiogram

Abstract: Sequences of different human cardiac rhythms terminating in ventricular fibrillation have been studied, both qualitatively and quantitatively, with methods of nonlinear dynamics. The analysis has been applied to ECG epochs belonging to rhythms of increasing electrocardiographic irregularity: from sinus rhythm to prefibrillatory rhythms and then to ventricular fibrillation. The phase portraits of these rhythms have been reconstructed from the ECG recording with the time-delay technique, and their correlation di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…This suggests that the nonlinear method can provide additional informative data for detecting epileptogenic foci. Moreover, the concordance of results between the nonlinear method and SPECT confirms the hypothesis that a loss of complexity appears when biological systems become functionally impaired [35]. …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This suggests that the nonlinear method can provide additional informative data for detecting epileptogenic foci. Moreover, the concordance of results between the nonlinear method and SPECT confirms the hypothesis that a loss of complexity appears when biological systems become functionally impaired [35]. …”
Section: Discussionsupporting
confidence: 56%
“…(2) EEG recorded during epileptic seizures showed nonlinear characteristics [15, 26, 33, 34]. (3) Some studies revealed that loss of complexity was related to functional impairment of the brain system [35, 36, 37], and decreased dimensional complexities of interictal EEG were observed in epileptic patients [27, 38, 39]. (4) Dimensional complexities of interictal EEG signals were higher than those of ictal EEG but lower than those of normal EEG [27].…”
Section: Methodsmentioning
confidence: 99%
“…The provocative cardiac chaos-control study by Garfinkel et al (15), combined with data suggesting that fibrillation is chaotic (43,44), sparked interest in nonlinear-dynamical control of fibrillation. However, other work has questioned the chaotic fibrillation hypothesis (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Chaotic phenomena have been observed in reaction-diffusion systems in chemistry [2], fundamental models of classical mechanics such as pendulum with periodic excitations [3], mathematical models describing fluid dynamics [4] and hydrodynamics [5]. Unique features of chaotic signals have been registered in brain activity [6] or electrocardiogram [7] data. The emergence of a population of different species in biology [8], commodity exchange in economy [9] and time-dependent models of many ecological situations [10] are other examples of dynamical systems that are subject to chaotic dynamics.…”
Section: Introductionmentioning
confidence: 99%